SPECIES COMPOSITION OF TORTOISES AND FRESHWATER TURTLES IN NINH THUAN PROVINCE, SOUTHERN VIETNAM - Tai Thang, Nguyen; Thi Tuyet Dung, Tran; Van Ha, Hoang; E. M. McCormack, Timothy; Thanh Luan, Nguyen (Journal of Forestry Science and Technology, 2022)
Chelonian diversity of Ninh Thuan province, South Central Coastal Vietnam, is still poorly understood. In this study, we conducted a semi-structured interview survey (2019) in 5 districts of Ninh Thuan province and a 7-day long field survey (2021) in Phuoc Binh National Park, Bac Ai district, Ninh Thuan province, as preliminary surveys to help contribute to current knowledge on the species diversity of tortoises and freshwater turtles in the province. As a result, 11 species of tortoise and freshwater turtle belonging to three (03) families account for 42.31% of the 26 total number of native tortoise and freshwater turtle species in Vietnam are likely to be distributed in Ninh Thuan province based on our findings. Of these, 9 species are threatened with extinction according to the IUCN Red List 2021 at the levels of Vulnerable (VU) (2 species), Endangered (EN) (3 species), and Critically Endangered (CR) (4 species). While 8 are listed in the Vietnam Red Book 2007, 5 VU, 2 EN, and 1 CR. Initial survey results also show that it is likely that the endemic and Critically Endangered Southern Vietnam Box Turtle (Cuora picturata) occurs in Phuoc Binh National Park, based on a shell specimen found in the wild for which genetic analysis is pending verification. Further surveys are still urgently needed to confirm Cuora picturata and other species in the wild and to better complete the list of tortoise and freshwater turtle species and their distributions within Ninh Thuan province.